2010
DOI: 10.1007/s11615-010-0011-2
|View full text |Cite
|
Sign up to set email alerts
|

Sachpolitik oder Parteipolitik?

Abstract: Zusammenfassung:In diesem beitrag untersuchen wir das Abstimmungsverhalten der länder bei namentlichen Abstimmungen im bundesrat im Zeitraum von der deutschen Wiedervereinigung 1990 bis zum Ende der Regierung gerhard Schröders 2005. Wir gehen der Frage nach, ob und wenn ja, wann und in welchem Ausmaß der bundesrat parteipolitisiert ist. Analytisch geht es um die Frage, wie ein durch originär sachpolitische Interessen motiviertes Verhalten von einem solchen unterschieden werden kann, das sich ausschließlich am … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The stenographic protocols of the plenary sessions are publicly available, but they do not register the individual voting behavior of the Länder. This only occurs in rare cases when the rollcall votes are requested or obligatory for constitutional amendments [26]. Recently, Länder governments have started to publish their voting behavior online.…”
Section: Tracing Decision-making In the German Bundesratmentioning
confidence: 99%
“…The stenographic protocols of the plenary sessions are publicly available, but they do not register the individual voting behavior of the Länder. This only occurs in rare cases when the rollcall votes are requested or obligatory for constitutional amendments [26]. Recently, Länder governments have started to publish their voting behavior online.…”
Section: Tracing Decision-making In the German Bundesratmentioning
confidence: 99%
“…The stenographic protocols of the plenary sessions are publicly available, but they do not register the individual voting behavior of the Länder. This only occurs in the rare cases when the roll-call votes are requested or obligatory for constitutional amendments (Bräuninger et al 2010). Recently, Länder governments have started to publish their voting behavior online.…”
Section: Tracing Decision-making In the German Bundesratmentioning
confidence: 99%
“…Political party coordination in the Bundesrat has mainly been discussed in a vertical direction, with some scholars arguing that the federal state government or opposition parties try to use their majorities in the Bundesrat to support or block legislation and with some scholars assessing whether political party or L€ ander interests prevail (Br€ auninger, Gschwend, and Shikano 2010;Lehmbruch 2000;Leunig and Tr€ ager 2014). In a horizontal direction, it has been observed that the political parties repeatedly meet (in so called A-[Social Democrats], B-[Christian Democrats] and recently also G-[Greens] meetings) 8 to coordinate their positions in the Bundesrat (Schrenk 2010;Leonardy 2002;Auel 2014).…”
Section: Political Party Coordinationmentioning
confidence: 99%
“…How do the members of the Bundesrat coordinate with each other? Building on research which shows that the interests of the L€ ander governmental actors play a role in Bundesrat decisions (Leunig and Tr€ ager 2014;Br€ auninger, Gschwend, and Shikano 2010), this article conceptualizes three interest dimensions of sub-state governmental actors, namely sectoral, territorial, and political party dimensions, and analyzes their consequences for the conduct of the coordination process. I then theoretically elaborate and empirically test which of these coordination strategies prevails over the others, thereby also including a time factor.…”
mentioning
confidence: 99%